High Efficient and Environment Friendly Plasma-Enhanced Synthesis of Al2O3-Coated LiNi1/3Co1/3Mn1/3O2 With Excellent Electrochemical Performance - Wang, Xinzhi; Jiang, Qianqian; Zhang, Yichi; Yuan, Nannan; Tang, Jianguo (Frontiers in Chemistry, 2020)
PLA-1-Al2O3@LNCM synthesized using an efficient and facile plasma-enhanced method exhibits markedly improved capacity retention of 98.6% after 100 cycles, which is much larger than that of LNCM at 80% after 100 cycles. What is more, it also exhibits significantly enhanced cyclicity compared to that of 1-Al2O3@LNCM cathodes prepared using the normal solid state method, which further illustrates the efficiency and superiority of this plasma-enhanced method. More importantly, the rate performance of PLA-1-Al2O3@LNCM is improved because of the better electrolyte storage of the assembled hierarchical architecture of the Al2O3 coating layer according to unimpeded Li+ diffusion from electrode to electrolyte. When cycling at 55°C, the PLA-1-Al2O3@LNCM shows 93.6% capacity retention after 100 cycles, which is greatly enhanced due to the uniform Al2O3 layer. Further, growth of polarization impedance during cycling can be effectively suppressed by the Al2O3 layer, which can further confirm the effect the Al2O3 layer coated on the surface of the LNCM. The enhanced cycling performance and thermal stability illustrates that this facile surface modification, using the plasma-enhanced method, can form an effective structured coating layer, which indicates its prospects as an application in the modification of other electrode materials.